Durban's 100 Resilient Cities journey: governing resilience from within. (October 2020) - Roberts, Debra; Douwes, Joanne; Sutherland, Catherine; Sim, Vicky
Urban resilience is the focus of a global policy discourse that is being mobilized by a wide range of organizations to reduce urban risk and respond to the shocks and stresses facing cities. This paper explores the process of "governing for resilience" through Durban's resilience journey as part of the 100 Resilient Cities (100RC) programme. From an insider perspective, it presents both 100RC and Durban's approaches to developing a resilience strategy. It reflects on the contestations that emerged as Durban and 100RC struggled over the meaning and practice of urban resilience. The paper develops a continuum of urban resilience approaches to analyse the conflicts that emerged as the global programme of urban resilience travelled to, and landed in, a South African city. The paper argues that a global framing of urban resilience needs to be responsive to a world of cities that share common risk trajectories but have different contexts and vulnerabilities. (1)